AI Brain Fry: How Artificial Intelligence Is Reshaping Human Cognition at Work. - Wiederhold, Brenda K. (CyberPsychology, Behavior & Social Networking, 2026)
The article focuses on the emerging phenomenon of "AI brain fry," a form of acute mental fatigue experienced by employees who interact extensively with artificial intelligence (AI) systems in the workplace. While AI automates routine tasks, it simultaneously shifts human roles toward supervising, evaluating, and correcting AI outputs, increasing cognitive demands such as attention, working memory, and decision-making. This redistribution of cognitive effort can lead to information overload, task switching, and mental exhaustion, potentially undermining employee well-being and productivity despite AI’s efficiency gains. The article emphasizes the importance of thoughtful AI integration, including training, workflow design, and cognitive ergonomics, to protect human cognition and suggests that immersive technologies like virtual reality and biofeedback may help mitigate AI-related cognitive overload.